Novel approach for UPLC-ESI-Tandem mass spectrometric method for simultaneous determination of olmesartan medoxomil and hydrochlorothiazide in their pharmaceutical combination with kinetic studies of forced degradation - Mostafa, Ahmed Abdalazim; Abou-El Alamin, Maha Mahmoud (European Journal of Chemistry, 2016)
A simple, robust ultra-performance liquid chromatography coupled to ESI-Tandem mass spectrometric (UPLC-MS/MS) technique was developed for the simultaneous quantitation of olmesartan medoxomil (OLM) and hydrochlorothiazide (HCT) in bulk and their combined pharmaceutical formulation. Chromatographic separation was done on a Hypersil gold 50×2.1 mm (1.9 μm) column, with gradient elution of mobile phase consisted of acetonitrile and 0.1% formic acid aqueous solution. Detection of analytes was carried out using selective reaction monitoring (SRM) mode on a triple quadrupole mass spectrometer coupled with electrospray ionization (ESI). Linearity was achieved over concentration ranges of 2.0-200.0 and 3.0-50.0 ng/mL for OLM and HCT, respectively. Intra and inter day reproducibility were acceptable. The lower limits of detection were found to be 0.627 and 0.583 ng/mL and lower limits of quantitation were 1.900 and 1.767 ng/mL for OLM and HCT, respectively. The method was successfully applied for determination the cited drugs in their combined pharmaceutical dosage form. The method was applied to study the kinetic of forced degradation of both drugs under different conditions. The method was validated according to ICH guidelines and there is no significance difference between the proposed method and the reported method. The simplicity and sensitivity of this method allows the utilization of method in quality control of the cited drugs.